„…читая в ногу души прекрасные порывы”: смех аутсайдера и русский ХХ век в Неизвестных письмах Олега Юрьева - Voloshchuk, Ievgeniia (Studia Rossica Posnaniensia, 2022)
The paper deals with the specifics of outsiders’ laughter in the book Unknown letters (Неизвестные письма/Unbekannte Briefe, Russian 2014, German 2017) by a Russian-German writer Oleg Yuryev. In particular, it analyzes how Russian cultural and historical traumas of the 20th century were reinterpreted in the book from the perspective of an ironical outsider. In doing so, it focuses on a fictional letter by the writer Leonid Dobychin, which is contextualized with fictional letters of Jakob Michael Reinhold Lenz and Ivan Pryzhov, representing previous historical and cultural periods. Yuryev’s ironic reflections on the Russian historical reality and literary scene of the 20th century manifest themselves at different levels, from the positioning of outsiders’ laughter in relation to the official and marginal hierarchies of the literary canon to the postmodernist play with the traditions of literary classics. In addition, the paper addresses the inter- and/or transcultural aspect of outsiders’ laughter in Yuryev’s book.